2019
DOI: 10.4236/tel.2019.94065
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Governance Practices: Evidence from MENA Countries

Abstract: This study investigates the level of compliance and disclosure of corporate governance mechanisms in Middle East and North Africa countries. The study uses a panel data of 250 companies from MENA countries between 2009 and 2016. The ordinary least square multiple regression analysis technique is used to examine the relationships. Additionally, to alleviate the concern of potential endogeneity, we use fixed effect regression, two-stage least squares using instrumental variables. The results show that the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It was also confirmed that this is largely the case in Hong Kong, where members of founding families are directors and executives of their firms and own the majority of the stock (Chen and Jaggi, 2000;AlHares, 2017). Theoretically, when managers own most of the firm's stocks, this can accentuate the free rider issue in that there is less monitoring of management, and there is risk of takeover by management (Shleifer and Vishny, 1997;AlHares et al, 2019). However, an alternative explanation is provided by several studies for the role of directors and management entrenchment.…”
Section: Do and Randd Intensitymentioning
confidence: 99%
“…It was also confirmed that this is largely the case in Hong Kong, where members of founding families are directors and executives of their firms and own the majority of the stock (Chen and Jaggi, 2000;AlHares, 2017). Theoretically, when managers own most of the firm's stocks, this can accentuate the free rider issue in that there is less monitoring of management, and there is risk of takeover by management (Shleifer and Vishny, 1997;AlHares et al, 2019). However, an alternative explanation is provided by several studies for the role of directors and management entrenchment.…”
Section: Do and Randd Intensitymentioning
confidence: 99%
“…Recent research in Middle East area also provide evidence that the cognitive creativity of internal audit has a significant role in detecting creative accounting practices [16]. Another study that is conducted on MENA countries showed that the applications of corporate governance and volumetry discloser is still low in MENA region and it varies among countries in this area [17]. Al-Hajaya [18] examined the effect of audit committee on enhancing audit quality as one of the main tools of corporate governance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies in countries with this type of legal system would not have to engage in as much monitoring as companies in countries where this information is missing. Therefore, the cost of capital in countries with good legal systems would be relatively low (Hail & Leuz, 2006;AlHares et al, 2019;Li & Mohanram, 2014;Hou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%